Аналіз біохімічного складу свіжих та свіжозаморожених плодів черешні трьох строків достигання, що вирощені в умовах Південного Степу України - Іванова, Ірина Євгенівна; Иванова, Ирина Евгеньевна; Ivanova, Iryna; Герасько, Тетяна Володимирівна; Герасько, Татьяна Владимировна; Herasko, Tetiana; Долгова, С. В. (Херсон: Вид. дім "Гельветика", 2019)
UK: Проведено аналіз біохімічного складу свіжих плодів черешні сортів раннього, середнього та пізнього строків достигання за показниками: сума цукрів, уміст сухих розчинних речовин, сума БАР. У заморо-жених сортозразках 3-х строків достигання визначено параметр – величина втрати соку. RU: Проведен анализ биохимического состава свежих плодов черешни сортов раннего, среднего и позднего сроков созревания по показателям: сумма сахаров, содержание сухих растворимых веществ, сумма БАВ. В замороженных сортообразцах 3-х сроков созревания определен параметр – величина потери сока. EN: The biochemical composition of fresh fruits of sweet cherry varieties of early, medium and late ripening periods are analyzed by using the indicators: total sugars, the content of dry soluble substances, the amount of BAS. It was defined the parameter, the value of the juice loss in the frozen varieties samples of 3 ripening periods.
Анализ биохимического состава свежих и свежезамороженных плодов черешни трех сроков созревания, выращенных в условиях южной степной зоны Украины
The analysis of the biochemical composition of fresh and fresh frozen sweet cherry fruits of the three ripening periods grown in the conditions of the Southern Steppe of Ukraine
Keywords: плоди черешні; строк достигання; біохімічний склад; заморожені сортозразки; дефростація; біологічно активні речовини; плоды черешни; срок созревания; биохимический состав; замороженные сортообразцы; дефростация; биологически активные вещества; sweet cherry fruits; ripening period; biochemical composition; frozen varieties samples; defrosting; biologically active substances